2013
DOI: 10.1371/journal.pone.0061427
|View full text |Cite
|
Sign up to set email alerts
|

High SOX2 Levels Predict Better Outcome in Non-Small Cell Lung Carcinomas

Abstract: BackgroundSOX2 is an embryonic developmental transcription factor, which is important in the development of the respiratory tract. SOX2 overexpression is associated with aggressive disease in several tumor types. However, SOX2 overexpression and gene amplification associates with favorable outcome in lung squamous cell carcinomas (SCC) and dissimilar results have been reported in lung adenocarcinomas (ADC). The aim of the present study was to evaluate SOX2 expression in NSCLC and determine the relationship wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 24 publications
7
35
1
Order By: Relevance
“…The results of the present study showed that the expression of SOX2 in NSCLC tissues was higher than that in the para-carcinoma tissues and a high SOX2 expression mainly occurred in lung squamous cell carcinoma cells. The study results were consistent with those of European and Japanese investigators (11,13). …”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study showed that the expression of SOX2 in NSCLC tissues was higher than that in the para-carcinoma tissues and a high SOX2 expression mainly occurred in lung squamous cell carcinoma cells. The study results were consistent with those of European and Japanese investigators (11,13). …”
Section: Discussionsupporting
confidence: 92%
“…16,53,55,57,68 For lung cancer, the proposed mechanism involves squamous maturation and thus improved response to chemotherapy. 69,70 The current study is the first report linking Sox2 amplification to improved outcome in serous ovarian cancer. In this model, we proposed a novel p53-dependent mechanism involving Sox2, Nanog, and Oct4 to explain the improved outcome noted in serous ovarian cancer.…”
Section: Discussionmentioning
confidence: 78%
“…Of which, 19 articles reported SOX2 DNA amplification and/or protein expression [1316, 37–51], six articles reported Nestin protein expression, and none reported Nestin DNA amplification [21, 5256]. In addition, Velcheti et al [46] and Iijima et al [50] reported two independent cohorts, respectively, and each cohort was considered as independent study in the meta-analysis. The included studies were published from 2010 to 2015 and the sample size ranged from 33 to 758.…”
Section: Resultsmentioning
confidence: 99%